Nudes : internet, socializações e afetividades na contemporaneidade - Machado, Nealla Valentim (2022)
In our interconnected society, erotic images produced in an intimate, affective/sexual environment are highlighted in the scope of the affection market in contemporary relationships. This thesis aims to comprehend how gender visibilities are negotiated in the affection market through the exchange of intimate images, namely nudes. Our goal is to understand how nudes compose the socialization processes and the online subjectivities nowadays. We also aim to understand questions such as how gender and sexuality present themselves in these socialization processes, taking into consideration other intersectional factors that permeate these online subjectivity constructions through the exchange of nudes. Digital social networks accelerate and multiply the possibilities to construct and give visibility to subjects in contemporaneity. Gender and sexuality are fundamental parts of these subjects' constitutions, simultaneously violence and oppression also play a role in these spaces. By using the help of a directed questionnaire, which resulted in more than 400 answers, and also through 10 videoconference in-depth interviews, we sought to understand how nudes are able to act as a motivator to create desires and erotic delight, becoming an important major part of the construction of amorous /sexual relationships in contemporaneity. We have analyzed taking into consideration intersectional perspectives the participants’ socio-economic profile, with data including age, location, internet access, race, gender, sexuality, and how people organize their affective/sexual relationships. From this data, we concluded that the participants were used to establishing these socialities through the exchange of images; how consent, desire, affect, seduction, and corporeality matters establish themselves among these exchanges; and from these movements, grasp the sociality through nudes in the capitalist logic of the affection market. Sending nudes is a behavior that has established itself into the liberal/neoliberal dynamics, which supposes the creation or invention of new visibilities to the subjects online as well as the settlement of old persistent restrictions related to morality and sexuality. Pleasure and danger remain combined in eroticism, expressing power asymmetry correlated to all the intersectional markers. The hierarchies remain delimited by the same structure that produces social, political, and economical inequalities within the neoliberal/liberal logic of the constitution of the subject.